Design and validation of a PISA oriented instructional module for linear functions aligned with the merdeka curriculum - Eka, Firmina; Suratman, Dede; Rifat, Mohammad; Siregar, Nurfadilah; Hamdani (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to design and validate a PISA-oriented instructional module for linear functions aligned with the Learning Outcomes of the Merdeka Curriculum. Method: This study employed a qualitative educational design research approach through document analysis and expert validation. The design process was based on an analysis of the Merdeka Curriculum Learning Outcomes (Phase D), the PISA 2022 Mathematics Framework, and relevant linear function materials. The instructional module was developed iteratively and validated in two cycles by two mathematics education lecturers and one junior high school mathematics teacher. Validation criteria covered content accuracy, pedagogical alignment, integration of PISA competencies, linguistic clarity, and instructional design quality. Findings: The needs analysis indicated that teachers did not yet possess structured PISA-based instructional modules. The first validation cycle highlighted the need to improve the clarity of learning objectives, interpretation-oriented tasks, activity differentiation, language consistency, and visual presentation. After systematic revisions, the second validation cycle confirmed that the module met feasibility standards across content, pedagogy, language, and instructional design aspects. Significance: This study provides a validated instructional module that bridges national curriculum demands and international mathematical literacy standards, offering a practical and theoretically grounded reference for integrating PISA-oriented learning into classroom instruction.